Relasi Konfilk dan Agama Studi Tentang Model Penyelesaian Konflik Kegamaan - Asnawan Asnawan (STAIFAS-Press, 2018)
ABSTRACT Several attempts to resolve the Sunni-Shi'a conflict pursued by various post-conflict groups include: 1) coordination meetings at the Muspida level by involving various elements in order to reduce wider conflict; 2) increase the intensity of communication between ethnic groups and groups in an effort to anticipate provocative issues; 3) crack down on the perpetrators and the brain of riots through efforts to find, detain Keywords: conflict, religion, Sunni-Shi'ah